Materials for creating tissue-engineered constructs using 3D bioprinting: cartilaginous and soft tissue restoration - N. V. Arguchinskaya; E. E. Beketov; E. V. Isaeva; N. S. Sergeeva; P. V. Shegay; S. A. Ivanov; A. D. Kaprin (Вестник трансплантологии и искусственных органов)
3D Bioprinting is a dynamically developing technology for tissue engineering and regenerative medicine. The main advantage of this technique is its ability to reproduce a given scaffold geometry and structure both in terms of the shape of the tissue-engineered construct and the distribution of its components. The key factor in bioprinting is bio ink, a cell-laden biocompatible material that mimics extracellular matrix. To meet all the requirements, the bio ink must include not only the main material, but also other components ensuring cell proliferation, differentiation and scaffold performance as a whole. The purpose of this review is to describe the most common materials applicable in bioprinting, consider their properties, prospects and limitations in cartilage restoration.